Exploring the Effectiveness of Educaplay in Evaluating Arabic Vocabulary: Student and Teacher Perspectives - Khotimah, Muti Husnul; Nasution, Sahkholid (STUDI ARAB, 2025)
Evaluation is a crucial part of the learning process, from the evaluation carried out it will be seen to what extent students are able to understand the lesson. Through an evaluation media in the form of a game, it is easier for teachers and students to conduct learning evaluations. The main problem examined in this study is how the experience, perception, and effectiveness of using the educational game educaplay as a medium for evaluating Arabic vocabulary are seen from the perspective of students and teachers. The approach used in this study is a qualitative approach with a descriptive method, the instruments used in this study are interviews and questionnaires. The data analysis technique used is the Milles and Hubberman model. This study was conducted at one of the Madrasah Aliyah Laboratory of the State Islamic University of North Sumatra Medan, the subjects in this study were 40 students and 1 teacher who taught Arabic. The results of this study were that most students were interested in evaluating using educaplay, and said that educaplay could help test students' abilities and was effective as a medium for evaluating Arabic vocabulary.